2010
DOI: 10.1055/s-0030-1248089
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Perceived Outcomes and Return to Sport and Work: TKA Versus Mini-Incision Unicompartmental Knee Arthroplasty

Abstract: Few reports have been published about patient-perceived outcomes and return to sport following total knee arthroplasty (TKA) compared with unicompartmental knee arthroplasty (UKA). This article compares the two procedures using self-assessment questionnaires to determine whether there was a difference in patient-perceived Oxford scores, return to sport, and return to work.Patient-perceived outcomes of mini-incision UKA (Oxford; Biomet Inc, Warsaw, Ind) and TKA were retrospectively reviewed at a minimum of 12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 14 publications
4
73
1
4
Order By: Relevance
“…UKA advocates purport a marginally better functional outcome over TKA [5,20,62]. This study confirms previous reports of patients with UKA having higher absolute postoperative clinical outcome measures (SF-12, WOMAC, KSCRS).…”
Section: Discussionsupporting
confidence: 88%
“…UKA advocates purport a marginally better functional outcome over TKA [5,20,62]. This study confirms previous reports of patients with UKA having higher absolute postoperative clinical outcome measures (SF-12, WOMAC, KSCRS).…”
Section: Discussionsupporting
confidence: 88%
“…Although TKA is one of the most commonly and increasingly performed surgical procedures in the world, there is limited information for younger, high-demand patients in regard to return to work ( Table 4). The existing published studies on return to work after TKA are limited by several factors: (1) there is a wide range in expected recovery time after knee arthroplasty in published studies ranging from 4 to 9 weeks in three US studies [9,17,18] to as high as 12 months in one study [2]; (2) the patient cohorts were small (\ 120 TKAs) [2,4,9,10]; (3) the average patient age was older than 65 years [3,13,18,19]; (4) the study included low-demand patients [3,4,13,18,19]; (5) the study was reported in the literature more than 10 years ago [4,13,19]; and (6) the study was not designed specifically to analyze return to work [3,9,19]. The purpose of this multicenter study was to determine whether young patients who were working before undergoing primary TKA are able to return to work postoperatively and to determine whether the patient's preoperative job physical demand category has an effect on ability to return to work.…”
Section: Discussionmentioning
confidence: 99%
“…In many patients, the desire for improvement in function often includes a desire to return to sports activities. The Oxford III UKA is a cruciate retaining arthroplasty with better kinematics [7] and good function [24]. Many patients commented that their Oxford UKA felt like a "normal knee".…”
Section: Discussionmentioning
confidence: 99%